PHARMACOGNOSTIC AND PHYTOCHEMICAL EVALUATION OF VAISHVANARA CHURNA - Usha, Patil (International Journal of Ayurveda and Pharma Research, 2016)
Vaishvanara churna is an Ayurvedic classical formulation prescribed in the management of Amavata (Rheumatoid arthritis) and digestive disorders. Though the drug is being used extensively in Ayurvedic practice for management of various disease conditions, its standards are not set as per the pharmacopeia. To maintain the uniformity in the efficacy of the medicine it is necessary to establish the quality standards so that the product can be screened at the point of production. To determine the standards for quality evaluation of Vaishvanara churna pharmacognostic, phytochemiacl, photomicrographic and analysis of aqueous and alcoholic extractives were determined. Further, the microbial quality of the Churna was also found to be well within the maximum limit proscribed by the WHO and the European Pharmacopeia. As there are no standards prescribed for the combined formulations, the values observed in the present study may be considered as acceptable before the final product is cleared from the production unit. Presence of higher active phytoconstituents and higher concentrations in aqueous compare to alcoholic extracts suggested the scientific reason behind the recommendation of Vaishvanara churna administration in water medium.